Sympathoexcitation Associated with Renin-Angiotensin System in Metabolic Syndrome - Takuya Kishi; Yoshitaka Hirooka (International Journal of Hypertension)
Renin-angiotensin system (RAS) is activated in metabolic syndrome (MetS), and RAS inhibitors are preferred for the treatments of hypertension with MetS. Although RAS activation is important for the therapeutic target, underlying sympathetic nervous system (SNS) activation is critically involved and should not be neglected in the pathogenesis of hypertension with MetS. In fact, previous studies have suggested that SNS activation has the interaction with RAS activation and/or insulin resistance. As a novel aspect connecting the importance of SNS and RAS activation, we and other investigators have recently demonstrated that angiotensin II type 1 receptor (AT1R) blockers (ARBs) improve SNS activation in patients with MetS. In the animal studies, SNS activation is regulated by the AT1R-induced oxidative stress in the brain. We have also demonstrated that orally administered ARBs cause sympathoinhibition independent of the depressor effects in dietary-induced hypertensive rats. Interestingly, these benefits on SNS activation of ARBs in clinical and animal studies are not class effects of ARBs. In conclusion, SNS activation associated with RAS activation in the brain should be the target of the treatment, and ARBs could have the potential benefit on SNS activation in patients with MetS.